Barium sulfate nanofiber-based high-temperature-resistant battery diaphragm as well as preparation method and application thereof
Through the composite structure of barium sulfate nanofibers and cellulose nanofibers, the problems of poor wetting and insufficient thermal stability of the lithium-ion battery separator are solved, which significantly improves the electrochemical performance and safety of the battery and extends the battery cycle Lifespan and rate performance.
Patent Information
- Application Number
- CN202411172846.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The electrolyte of the existing lithium-ion battery separator has poor wetting, low liquid absorption, low ion conductivity, unsatisfactory battery circulation and rate performance, and poor thermal stability, which poses safety hazards at high temperatures.
The diaphragm is prepared by a composite nanofiber network structure formed by hydrogen bonding and van der Waals winding, which improves the high temperature and flame retardant properties of the diaphragm, enhances the electrolyte infiltration and adsorption properties, and improves the ion transport capability.
It significantly improves the electrochemical performance and safety of the battery, improves the tensile strength, porosity and electrolyte adsorption rate of the diaphragm, extends the cycle life and rate performance of the battery, and reduces safety hazards at high temperatures.
Smart Images

Figure CN119133774A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery material preparation, and specifically relates to a barium sulfate nanofiber-based high-temperature resistant battery and a preparation method and application thereof. Background Art
[0002] Common lithium batteries such as lithium-ion batteries and lithium metal batteries have the advantages of high energy density, high power density and long cycle life, and are therefore widely used in portable electronic devices, new power batteries and energy storage batteries. The battery is mainly composed of four parts: positive electrode, negative electrode, separator and electrolyte. As one of the important components in the battery, the separator plays a role in preventing the positive and negative electrodes from directly contacting each other and causing a short circuit in the battery. On the other hand, it plays a role in regulating and controlling ion transmission. The performance of the separator has a direct impact on the battery's ion transmission rate, ion transmission pathway, electron transfer, interface structure, impedance, etc., which in turn affects the battery's capacity, rate performance and cycle life. In addition, the high-temperature stability of the separator can directly determine the safety of the battery. A separator with high-temperature stability can avoid the safety hazards of rapid heating and even explosion of the battery.
[0003] With the increasing popularity of electric vehicles and new portable electronic devices in daily life, lithium-ion batteries are required to have longer cycle life, stronger endurance, wider operating temperature range and be more economical and environmentally friendly. As an indispensable part of lithium-ion batteries, the diaphragm can affect important parameters such as the capacity, cycle performance and service life of lithium-ion batteries.
[0004] Currently, commercial battery separators can be divided into several categories: microporous polyolefin membranes, non-woven separators, and inorganic composite separators. The commercial separators widely used in lithium batteries are microporous polyolefin separators. Such separators are cheap, have high tensile strength, and have good electrochemical stability. However, the disadvantages of such separators are also very obvious: (1) The polarity of polyolefin separators is weak, and the electrolyte is often an organic solvent system with strong polarity. When the electrolyte contacts the polyolefin separator, the separator is almost difficult to be infiltrated by the electrolyte. Therefore, the polyolefin separator exhibits poor electrolyte affinity, which in turn has an adverse effect on the battery's capacity, rate performance, cycle life and other performance. (2) Polyolefin separators are often obtained by melt stretching. This method requires the separator to have a certain mechanical strength, but this method often causes the polyolefin separator to have Low porosity (the porosity of polyolefin separators is generally less than 60%), which will reduce the ion transfer rate and ion transfer quantity of the battery, making the battery have a large internal resistance, resulting in unsatisfactory electrochemical performance; (3) It is well known that polyolefin separators have poor high temperature resistance. Most polyolefin separators are difficult to withstand high temperatures above 150°C. When the temperature is high, they will shrink or melt, resulting in direct contact between the positive and negative electrodes, causing battery short circuits, and even causing battery combustion or explosion in severe cases. Therefore, polyolefin separators have high safety risks. Although some separators can self-close at high temperatures, they will pose safety risks when the thermal shock is large. Therefore, it is urgent to develop a high-performance battery separator with good electrolyte wettability, uniform separator thickness, high ionic conductivity, high porosity, uniform pore structure, strong mechanical properties and excellent thermal stability. Summary of the Invention
[0005] In view of the significant shortcomings of ordinary polyolefin-based membranes in the prior art, such as poor electrolyte wettability, low liquid absorption rate, low ionic conductivity, unsatisfactory battery cycle performance and rate performance, and poor thermal stability, the present invention aims to provide a barium sulfate nanofiber-based high-temperature resistant battery membrane and its preparation method and application, so as to improve the thermal stability and flame retardant properties of the battery membrane, improve the membrane's wetting and adsorption properties for electrolyte, and improve the membrane's ionic conductivity and plasma transmission capacity, thereby improving the electrochemical performance and safety of the battery.
[0006] Barium sulfate, as an inorganic compound, possesses excellent chemical stability and high-temperature and fire resistance. Separators made with barium sulfate nanofibers exhibit excellent thermal stability and flame retardancy. Therefore, incorporating barium sulfate nanofibers into battery separators can effectively enhance their high-temperature resistance and flame retardancy, significantly improving battery safety.
[0007] In the first aspect, the present invention provides a barium sulfate nanofiber-based high-temperature resistant battery separator, which is a hybrid composite nanofiber network structure formed by barium sulfate nanofibers and cellulose nanofibers entangled together through hydrogen bonds and van der Waals forces; in terms of mass percentage, the content of the barium sulfate nanofibers is 20 to 100 wt%, and the content of the cellulose nanofibers is 0 to 80 wt%; preferably, the content of the barium sulfate nanofibers is 40 to 80 wt%, and the content of the cellulose nanofibers is 20 to 60 wt%.
[0008] Preferably, the diameter of the barium sulfate nanofiber is 5 to 200 nanometers; the length of the barium sulfate nanofiber is 20 to 2000 micrometers.
[0009] Preferably, the cellulose nanofiber is at least one of plant cellulose nanofiber and bacterial cellulose nanofiber.
[0010] Preferably, the thickness of the barium sulfate nanofiber-based high-temperature resistant battery separator is 10 to 200 μm.
[0011] Preferably, the tensile strength of the barium sulfate nanofiber-based high-temperature resistant battery separator is 4 to 100 MPa.
[0012] Preferably, the porosity of the barium sulfate nanofiber-based high-temperature resistant battery separator is 30% to 95%.
[0013] Preferably, the adsorption rate of the barium sulfate nanofiber-based high-temperature resistant battery separator to the electrolyte is 50% to 500%.
[0014] In a second aspect, the present invention provides a method for preparing a barium sulfate nanofiber-based high-temperature resistant battery separator, comprising: mixing an aqueous slurry of barium sulfate nanofibers, a cellulose nanofiber dispersion and a solvent to obtain a barium sulfate nanofiber composite slurry; filtering the obtained barium sulfate nanofiber composite slurry to form a membrane, separating and drying the slurry to obtain the barium sulfate nanofiber-based high-temperature resistant battery separator.
[0015] Preferably, the concentration of the aqueous slurry of barium sulfate nanofibers is not limited and can be any concentration.
[0016] Preferably, the solvent of the cellulose nanofiber dispersion is at least one of water and ethanol; the concentration of the cellulose nanofiber dispersion is not limited and can be any concentration.
[0017] Preferably, the concentration of the aqueous slurry of barium sulfate nanofibers is not limited and can be any concentration.
[0018] Preferably, the solvent is at least one of water, ethanol and isopropanol.
[0019] Preferably, the filtration is vacuum-assisted filtration.
[0020] Preferably, the drying temperature is 60-100° C. and the drying time is 6-24 hours.
[0021] In a third aspect, the present invention also provides a battery comprising the above-mentioned barium sulfate nanofiber-based high-temperature resistant battery separator.
[0022] Beneficial effects: The barium sulfate nanofiber-based high-temperature resistant battery separator prepared by the present invention has excellent properties, such as good electrolyte wetting performance, high electrolyte adsorption rate, excellent high-temperature resistance and flame retardancy, and good mechanical properties. It can effectively improve the battery's rate performance and cycle life, significantly improving battery safety. Therefore, the barium sulfate nanofiber composite high-performance high-temperature resistant separator can be used in lithium-ion batteries, lithium metal batteries (including lithium-sulfur and lithium-air batteries), and other power and energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a transmission electron micrograph of the barium sulfate nanofibers prepared in the present invention; Figure 2 This is a transmission electron micrograph of the bacterial cellulose nanofibers used in the present invention; Figure 3 These are photos of the barium sulfate nanofiber composite high-performance high-temperature resistant separator (BC-BS) of Example 1 and the polypropylene separator (PP) of Comparative Example 1 after being heated in an oven at 125°C, 150°C, and 175°C for 30 minutes, respectively; Figure 4 The following are photographs of the barium sulfate nanofiber composite high-performance, high-temperature resistant diaphragm (BC-BS) of Example 1 and the polypropylene diaphragm (PP) of Comparative Example 1 before and after 10 seconds of ignition; wherein, (a) is a photograph of the barium sulfate nanofiber composite high-performance, high-temperature resistant diaphragm before ignition; (b) is a photograph of the barium sulfate nanofiber composite high-performance, high-temperature resistant diaphragm after 10 seconds of ignition; (c) is a photograph of the polypropylene diaphragm before ignition; (d) is a photograph of the polypropylene diaphragm after 10 seconds of ignition; Figure 5 The results of rate performance tests of lithium iron phosphate-graphite batteries using the barium sulfate nanofiber composite high-performance high-temperature resistant separator (BC-BS) of Example 1 and the polypropylene separator (PP) of Comparative Example 1 at 0.2C, 0.5C, 1C, and 2C, respectively; Figure 6 The figures are the cycling test results of lithium iron phosphate-graphite batteries using the barium sulfate nanofiber composite high-performance high-temperature resistant separator (BC-BS) of Example 1 and the polypropylene separator (PP) of Comparative Example 1 at a 2C rate; Figure 7Figure 1 shows the thermal runaway behavior test results of lithium iron phosphate-graphite batteries using the barium sulfate nanofiber composite high-performance, high-temperature resistant separator (BC-BS) of Example 1 and the polypropylene separator (PP) of Comparative Example 1. (a) is a graph of self-heating temperature versus time; (b) is a graph of self-heating rate versus temperature. Figure 8 The display screen was powered at various bending angles using a lithium iron phosphate-graphite soft-pack full battery assembled with the barium sulfate nanofiber composite high-performance high-temperature resistant separator (BC-BS) of Example 1. DETAILED DESCRIPTION
[0024] To further illustrate the content, characteristics and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific embodiments. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification carried out by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention. Unless otherwise specified, each percentage refers to the percentage by mass.
[0025] In the present invention, the barium sulfate nanofiber-based high-temperature resistant battery separator is prepared by combining barium sulfate nanofibers and cellulose nanofibers. The barium sulfate nanofiber-based high-temperature resistant battery separator is a hybrid composite nanofiber network structure formed by barium sulfate nanofibers and cellulose nanofibers entangled together through hydrogen bonds and van der Waals forces; in terms of mass percentage, the content of the barium sulfate nanofibers is 20-100wt%, and the content of the cellulose nanofibers is 0-80wt%; preferably, the content of the barium sulfate nanofibers is 40-80wt%, and the content of the cellulose nanofibers is 20-60wt%. The present invention can regulate the tensile strength, porosity and adsorption rate of the barium sulfate nanofiber composite high-performance high-temperature resistant separator by regulating the weight ratio of barium sulfate nanofibers to cellulose nanofibers. If the content of barium sulfate nanofibers is too low, the specific capacity of the battery will be reduced, and if the content of barium sulfate nanofibers is too high, the pore structure characteristics and electrolyte wetting properties of the separator will be affected. The barium sulfate nanofibers have a diameter of 5 to 200 nanometers and a length of 20 to 2000 microns. The cellulose nanofibers are at least one of plant cellulose nanofibers and bacterial cellulose nanofibers. The diameter of the barium sulfate nanofiber-based high-temperature resistant battery separator can be controlled as needed, and the thickness of the barium sulfate nanofiber-based high-temperature resistant battery separator is 10 to 200 μm.
[0026] The barium sulfate nanofiber composite high-temperature-resistant battery separator prepared by the present invention has excellent high-temperature resistance and electrochemical properties, good electrolyte wetting performance, high porosity, high electrolyte adsorption rate, relatively uniform pore structure, mechanical strength that can meet normal use requirements, excellent thermal stability and flame retardancy, and can effectively improve the battery's fast charging capability, rate performance, cycle life, and battery safety. The barium sulfate nanofiber-based high-temperature-resistant battery separator has a tensile strength of 4 to 100 MPa; a porosity of 30% to 95%; and an electrolyte adsorption rate of 50% to 500%.
[0027] Barium sulfate, as an inorganic compound, has excellent chemical stability, high temperature resistance and fire resistance. The diaphragm prepared using barium sulfate nanofibers has good flame retardant properties. Therefore, the application of barium sulfate nanofibers to battery diaphragms can effectively enhance the high temperature resistance and flame retardant properties of the diaphragm and significantly improve the safety of the battery. Cellulose nanofibers have a high dielectric constant. When voltage is applied, barium sulfate nanofibers will produce oriented dipoles. These dipoles help to form a uniform electric field at the interface between the diaphragm and the electrolyte, which is called MAX-Wagner polarization. The built-in electric field formed by this polarization can effectively regulate the lithium ion solvation structure at the diaphragm-electrolyte interface. In the present invention, the oriented electric field generated by combining barium sulfate nanofibers with cellulose nanofibers can attract the coordinated solvent molecules in the solvation sheath through dipole-dipole interactions, making it easier for hydrated lithium ions to break free from the constraints of the solvent molecules, thereby accelerating their transmission speed between the electrodes.
[0028] The invention adopts a vacuum filtration method to prepare a barium sulfate nanofiber-based high-temperature resistant battery separator, which has the advantages of simple operation, low cost, and easy mass production.
[0029] The following is an exemplary description of the method for preparing the barium sulfate nanofiber-based high-temperature resistant battery separator provided by the present invention.
[0030] The barium sulfate nanofibers of the present invention can be prepared by a hydrothermal method, and can be prepared by referring to the methods reported in published patents and literature, for example: Zhu Yingjie, Wu Jin, A barium sulfate fiber and its preparation method, patent number CN202010705516.1; Zhu Yingjie, Wu Jin, A barium sulfate fiber inorganic refractory paper and its preparation method and application, patent number CN202010705522.7; Jin Wu, Ying-Jie Zhu, Eur. J. Inorg, 2021, 429-499 (2020). The hydrothermal method comprises: (1) using oleate as a reactant and an emulsifier, a water-soluble barium salt as a barium source, and water as a solvent to obtain a barium oleate precursor suspension through a chemical reaction. The water-soluble barium salt can be selected from at least one of barium chloride and barium nitrate. The oleate can be selected from at least one of sodium oleate, potassium oleate, and ammonium oleate. The present invention selects water as the reaction solvent, which is low in cost, environmentally friendly, and conducive to large-scale production. In the barium oleate precursor suspension, the concentration of oleate is 0.01 to 2 mol / L, preferably 0.1 to 1 mol / L; the concentration of water-soluble barium salt is 0.01 to 2 mol / L, preferably 0.03 to 1 mol / L. (2) Then, a water-soluble sulfate is added to the barium oleate precursor suspension to obtain a barium sulfate precursor suspension. The water-soluble sulfate can be selected from at least one of sodium sulfate, potassium sulfate and ammonium sulfate. The concentration of the water-soluble sulfate is 0.01 to 6 mol / L, preferably 0.1 to 1 mol / L. (3) The obtained barium sulfate precursor suspension is placed in a reactor, sealed, and subjected to hydrothermal treatment. The temperature of the hydrothermal treatment is 120 to 240°C, preferably 160 to 200°C. After separation, the product is washed several times with ethanol and water, and dried to obtain the barium sulfate nanofibers (such as Figure 1 Barium sulfate nanofibers, prepared by a hydrothermal method using a calcium oleate precursor, can intertwine with cellulose nanofibers to form a porous network structure, significantly improving the mechanical properties of the composite separator. As a separator material, these nanofibers can modulate ion transport properties through polarization electric fields, enhancing the performance of lithium-ion batteries. Other methods typically produce barium sulfate particles, which are difficult to prepare as separators.
[0031] The barium sulfate nanofiber composite slurry is prepared by mixing the barium sulfate nanofiber aqueous slurry, the cellulose nanofiber dispersion and the solvent in a certain proportion to obtain a uniformly dispersed barium sulfate nanofiber composite slurry.
[0032] In an optional embodiment, the solvent of the cellulose nanofiber dispersion is at least one of water and ethanol; the concentration of the cellulose nanofiber dispersion is not limited and can be any concentration.
[0033] In an optional embodiment, the cellulose nanofiber includes but is not limited to at least one of plant fiber and bacterial cellulose.
[0034] In an optional embodiment, the concentration of the aqueous slurry of barium sulfate nanofibers is not limited and can be any concentration.
[0035] In an optional embodiment, the solvent includes but is not limited to at least one of water, ethanol, and isopropanol.
[0036] The obtained barium sulfate nanofiber composite slurry is filtered to form a membrane. Specifically, the obtained barium sulfate nanofiber composite slurry is filtered and separated on a suction filter to obtain a wet barium sulfate nanofiber composite high-performance and high-temperature resistant separator for batteries.
[0037] Drying and post-processing: The wet barium sulfate nanofiber composite high-performance high-temperature resistant separator is dried and pressed (including roller pressing) to obtain a barium sulfate nanofiber composite high-performance high-temperature resistant separator for batteries.
[0038] In an optional embodiment, the drying temperature is 60-100° C. and the drying time is 6-24 hours.
[0039] The application scope of the barium sulfate nanofiber composite high-performance high-temperature resistant separator for batteries prepared by the present invention includes lithium-ion batteries, lithium metal batteries (including lithium-sulfur and lithium-air batteries), and other power and energy storage batteries.
[0040] The present invention uses a micrometer (with an accuracy of 0.01 mm) to test the thickness of the battery separator. Five points are randomly selected on the separator and the average value is calculated. A universal mechanical testing machine (Drick, DRK-101B) is used to test the tensile strength of the barium sulfate nanofiber composite high-performance and high-temperature resistant battery separator and the comparative battery separator. Specifically, the separator is cut into rectangular splines with a length of 40 mm and a width of 10 mm. The ends of the splines are clamped on the universal mechanical testing machine for tensile strength testing. The clamp movement speed is 1 mm / min and the clamp spacing is 15 mm. Porosity: The battery separator is soaked in n-butanol for 1 hour, and then the porosity is calculated according to the formula: Porosity (%) = (Δm / ρ) / V0×100%; where Δm is the difference between the weight of the separator after adsorbing n-butanol and the initial weight of the separator, V0 is the volume of the separator, and ρ is the density of n-butanol. The measurements are taken three times and the average value is calculated. Electrolyte Adsorption Rate: Soak the battery separator in the electrolyte for 30 minutes. Calculate the electrolyte adsorption rate (%) using the following formula: Electrolyte Adsorption Rate (%) = (M - M0) / M0 × 100%; where M0 is the initial weight of the separator and M is the weight of the separator after electrolyte adsorption. Perform three measurements and calculate the average.
[0041] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description herein, and are not limited to the specific numerical values exemplified below.
[0042] Example 1
[0043] At room temperature, 7 mg of 6.5 mg / ml aqueous slurry of barium sulfate nanofibers was dispersed in 50 mL of ethanol, 10.5 mg of 3.5 mg / ml bacterial cellulose nanofiber dispersion was added and stirred for 20 minutes, and then placed on a sand core funnel with a diameter of 40 mm for vacuum filtration. After drying at 60°C for 24 hours, the film was peeled off to obtain a barium sulfate nanofiber composite high-performance high-temperature resistant battery separator with a diameter of 40 mm and a thickness of 18 microns.
[0044] Figure 3 The following are photos of the barium sulfate nanofiber composite high-performance high-temperature resistant battery separator and the polypropylene separator after heat treatment in an oven at 125°C, 150°C and 175°C for 30 minutes, respectively. As can be seen from the figure, the polypropylene separator shows obvious thermal shrinkage at 125°C. At 175°C, the polypropylene separator completely turns into a transparent state, indicating that it has melted and closed the pores, completely losing its function. In contrast, the barium sulfate nanofiber composite high-performance high-temperature resistant battery separator did not shrink significantly at high temperatures of 125, 150 and 175°C, showing good thermal stability. Although the color of the barium sulfate nanofiber composite high-performance high-temperature resistant battery separator turns slightly yellow due to the oxidation of cellulose nanofibers at high temperatures, its shape and size can be kept intact. This shows that the barium sulfate nanofiber composite high-performance high-temperature resistant battery separator prepared by the present invention has excellent high-temperature resistance.
[0045] Figure 4 The following are photos of a high-performance, high-temperature-resistant, barium sulfate nanofiber composite battery separator and a polypropylene battery separator before and 10 seconds after burning. As can be seen from the figure, the surface color of the high-performance, high-temperature-resistant barium sulfate nanofiber composite battery separator deepens, but the intact membrane structure is still visible. In contrast, the polypropylene separator immediately curls up after contact with the flame of the alcohol lamp, quickly ignites, and burns out completely within a very short time (2 seconds). This shows that the high-performance, high-temperature-resistant, barium sulfate nanofiber composite battery separator prepared by the present invention has good flame retardant properties.
[0046] Example 2
[0047] At room temperature, 8.75 mg of 6.5 mg / ml aqueous slurry of barium sulfate nanofibers was dispersed in 50 mL of ethanol, and 8.75 mg of 3.5 mg / ml bacterial cellulose nanofiber dispersion was added. After stirring for 20 minutes, it was placed on a sand core funnel with a diameter of 40 mm for filtration. After drying and peeling off the film, a barium sulfate nanofiber composite high-performance and high-temperature resistant battery separator with a diameter of 40 mm and a thickness of 23 microns was obtained.
[0048] Example 3
[0049] At room temperature, 10.5 mg of 6.5 mg / ml aqueous slurry of barium sulfate nanofibers was dispersed in 50 mL of ethanol, and 7 mg of 3.5 mg / ml bacterial cellulose nanofiber dispersion was added. After stirring for 20 minutes, it was placed on a sand core funnel with a diameter of 40 mm for filtration. After drying and peeling off the film, a barium sulfate nanofiber composite high-performance and high-temperature resistant battery separator with a diameter of 40 mm and a thickness of 18 microns was obtained.
[0050] Example 4
[0051] At room temperature, 6 mg of 6.5 mg / ml aqueous slurry of barium sulfate nanofibers was dispersed in 50 mL of ethanol, and 9 mg of 3.5 mg / ml bacterial cellulose nanofiber dispersion was added. After stirring for 20 minutes, it was placed on a sand core funnel with a diameter of 40 mm for filtration. After drying and peeling off the film, a barium sulfate nanofiber composite high-performance and high-temperature resistant battery separator with a diameter of 40 mm and a thickness of 18 microns was obtained.
[0052] Example 5
[0053] At room temperature, 8 mg of barium sulfate nanofiber slurry with a concentration of 6.5 mg / ml was dispersed in 50 mL of ethanol, and 12 mg of bacterial cellulose nanofiber dispersion with a concentration of 3.5 mg / ml was added. After stirring for 20 minutes, it was placed on a sand core funnel with a diameter of 40 mm for filtration. After drying and peeling off the film, a barium sulfate nanofiber composite high-performance and high-temperature resistant battery separator with a diameter of 40 mm and a thickness of 25 microns was obtained.
[0054] Comparative Example 1
[0055] A commercial polypropylene battery separator (24 μm thick and 42.9% porosity) was used as a comparison.
[0056] The battery separators in Examples 1-5 and Comparative Example 1 were characterized and tested for performance. Table 1 shows the performance parameters of the barium sulfate nanofiber composite high-performance, high-temperature resistant battery separators prepared in Examples 1-5 of the present invention and the polypropylene separator of Comparative Example 1.
[0057] Table 1:
[0058] As can be seen from Table 1, the porosity of the barium sulfate nanofiber composite high-performance high-temperature resistant battery separators prepared in Examples 1-5 of the present invention is greater than that of the polypropylene separator in Comparative Example 1, mainly due to the drawing process in the preparation process of the commercial polypropylene separator. These uneven, discontinuous, and serrated pore structure characteristics lead to a lower porosity of the commercial polypropylene separator. The barium sulfate nanofiber composite high-performance high-temperature resistant battery separator is composed of an ordered layered structure, which makes the separator have good porous properties that are conducive to the wetting and diffusion of liquid electrolytes. Except for Example 3, the electrolyte adsorption rate of the barium sulfate nanofiber composite high-performance high-temperature resistant battery separators prepared in Examples 1-2 and Examples 4-5 of the present invention is greater than that of the polypropylene separator in Comparative Example 1. This is because the barium sulfate nanofiber and cellulose nanofiber in Example 3 are in the optimal ratio.
[0059] Battery performance test (1) Preparation of battery positive electrode: The positive electrode materials tested for button-type full-cell and soft-pack full-cell (lithium iron phosphate-graphite battery) are all high-load lithium iron phosphate positive electrodes with a loading of 15.5 mg / cm 2 The electrode was punched to obtain a button battery positive electrode with a diameter of 12 mm. The lithium iron phosphate positive electrode was cut into a size of 3 cm × 3 cm to serve as a soft pack battery positive electrode. (2) Preparation of battery negative electrode: The negative electrode materials tested for button-type full-cell and soft-pack full-cell (lithium iron phosphate-graphite battery) are all high-load graphite negative electrodes with a loading of 7.5 mg / cm 2 The electrode sheet was punched to obtain a button battery negative electrode sheet with a diameter of 13 mm. The graphite negative electrode was cut into a size of 3 cm × 3 cm to serve as a soft pack battery negative electrode sheet; (3) Assembly of the battery. In a glove box filled with argon, the above-mentioned negative electrode sheet and battery separator are sequentially placed in the battery shell, 100 μL of electrolyte is added, the positive electrode sheet is placed, and the battery shell is sealed to obtain the battery. The electrolyte used for testing at room temperature is 1.2M LiPF6, and the solvent is ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 3:7, to which 2 wt.% of vinylene carbonate (VC) is added. The soft-pack battery is prepared by cutting the separator into a 3.5 cm × 3.5 cm square. In a glove box filled with argon, the above-mentioned spare electrodes and separators are assembled according to the structure of lithium iron phosphate / separator / graphite. The electrolyte is added before the final packaging, and the battery is packaged with aluminum plastic film.
[0060] Figure 5The figure shows the rate performance test results of lithium iron phosphate-graphite batteries using the barium sulfate nanofiber composite high-performance high-temperature resistant separator of Example 1 and the polypropylene separator of Comparative Example 1 at 0.2C, 0.5C, 1C, and 2C, respectively. As can be seen from the figure, the rate performance of high-load lithium iron phosphate / graphite full batteries with different separators is as high as 149.5 mAh g at 0.2C compared to the battery using the polypropylene separator. -1 The discharge capacity is better than that of the battery using polypropylene separator (capacity of 119.9 mAh g -1 ). This shows that the lithium iron phosphate-graphite battery prepared by using barium sulfate nanofiber composite high-performance high-temperature resistant battery separator has excellent rate performance.
[0061] Figure 6 The results of the cycling tests of lithium iron phosphate-graphite batteries using the barium sulfate nanofiber composite high-performance high-temperature resistant separator of Example 1 and the polypropylene separator of Comparative Example 1 at a rate of 2C are shown in the figure. As can be seen from the figure, the high-load lithium iron phosphate / graphite full battery with different separators has a high cycling rate of 2C (~10.8mA cm -2 ) under the accelerated charge / discharge current density. The battery using barium sulfate nanofiber composite high-performance high-temperature resistant separator showed a high initial discharge capacity of 123.3 mAh g -1 (or ~1.91 mAh cm -2 ), while the battery using standard polypropylene separator showed a lower initial discharge capacity of 103.8 mAh g -1 (approximately 1.60 mAh cm -2 ). It can be seen that the battery using barium sulfate nanofiber composite high-performance high-temperature resistant separator outperforms the battery using standard polypropylene separator by 18.7%. In addition, the battery using barium sulfate nanofiber composite high-performance high-temperature resistant separator maintains excellent cycle stability, achieving an impressive 70% capacity retention rate for up to 500 cycles. In sharp contrast, the battery using polypropylene separator exhibits significant capacity decay, with a retention rate of 49% after 150 cycles and a retention rate of 27% after 500 cycles. This shows that lithium iron phosphate-graphite batteries prepared with barium sulfate nanofiber composite high-performance high-temperature resistant battery separators have excellent cycle life.
[0062] Figure 7The following figures show the thermal runaway behavior of a fully charged lithium iron phosphate-graphite battery using the barium sulfate nanofiber composite high-performance, high-temperature-resistant separator from Example 1 and the polypropylene separator from Comparative Example 1, using an accelerating calorimeter. (a) shows a graph of self-heating temperature versus time; (b) shows a graph of self-heating rate versus temperature. As can be seen from the figures, the excellent thermal stability of the BS / BC separator can effectively increase the critical temperature for thermal runaway, reduce heat release, and significantly improve the battery's thermal safety. This demonstrates that lithium iron phosphate-graphite batteries assembled with the barium sulfate nanofiber composite high-performance, high-temperature-resistant battery separator have excellent high-temperature stability.
[0063] Figure 8 A lithium iron phosphate-graphite soft-pack full battery assembled with the barium sulfate nanofiber composite high-performance, high-temperature resistant separator (BC-BS) prepared in Example 1 was used to power a display screen at various bending angles. As shown in the figure, the lithium iron phosphate-graphite soft-pack full battery assembled with the barium sulfate nanofiber composite high-performance, high-temperature resistant separator (BC-BS) prepared in Example 1 can illuminate the display screen at various bending angles. This indicates that the lithium iron phosphate-graphite soft-pack full battery assembled with the barium sulfate nanofiber composite high-performance, high-temperature resistant separator (BC-BS) prepared in the present invention is not affected by bending angle and can operate normally at various bending angles.
Claims
1. A barium sulfate nanofiber-based high temperature resistant battery separator, characterized in that: The barium sulfate nanofiber-based high-temperature resistant battery separator is a hybrid composite nanofiber network structure formed by barium sulfate nanofibers and cellulose nanofibers entangled together through hydrogen bonds and van der Waals forces; in terms of mass percentage, the content of the barium sulfate nanofibers is 20 to 100 wt%, and the content of the cellulose nanofibers is 0 to 80 wt%; preferably, the content of the barium sulfate nanofibers is 40 to 80 wt%, and the content of the cellulose nanofibers is 20 to 60 wt%.
2. The barium sulfate nanofiber-based high temperature resistant battery separator according to claim 1, characterized in that: The diameter of the barium sulfate nanofiber is 5 to 200 nanometers; the length of the barium sulfate nanofiber is 20 to 2000 micrometers.
3. The barium sulfate nanofiber-based high temperature resistant battery separator according to claim 1 or 2, characterized in that: The cellulose nanofiber is at least one of plant cellulose nanofiber and bacterial cellulose nanofiber.
4. The barium sulfate nanofiber-based high temperature resistant battery separator according to any one of claims 1 to 3, characterized in that: The thickness of the barium sulfate nanofiber-based high-temperature resistant battery separator is 10 to 200 microns.
5. The barium sulfate nanofiber-based high temperature resistant battery separator according to any one of claims 1 to 4, characterized in that: The tensile strength of the barium sulfate nanofiber-based high temperature resistant battery separator is 4 to 100 MPa; The porosity of the barium sulfate nanofiber-based high temperature resistant battery separator is 30% to 95%; The adsorption rate of the barium sulfate nanofiber-based high-temperature resistant battery separator to the electrolyte is 50% to 500%.
6. A method for preparing a barium sulfate nanofiber-based high temperature resistant battery separator according to any one of claims 1 to 5, characterized in that: include: The barium sulfate nanofiber aqueous slurry, the cellulose nanofiber dispersion and the solvent are mixed to obtain the barium sulfate nanofiber composite slurry; The obtained barium sulfate nanofiber composite slurry is filtered to form a membrane, separated and dried to obtain the barium sulfate nanofiber-based high-temperature resistant battery separator.
7. The preparation method according to claim 6, characterized in that: The solvent of the cellulose nanofiber dispersion is at least one of water and ethanol; The solvent is at least one of water, ethanol and isopropanol.
8. The preparation method according to claim 6 or 7, characterized in that: The filtration is vacuum-assisted filtration; The drying temperature is 60-100° C. and the drying time is 6-24 hours.
9. A battery comprising the barium sulfate nanofiber-based high temperature resistant battery separator according to any one of claims 1 to 5.
Citation Information
Patent Citations
Wood pulp fiber / nanometer barium sulfate composite lithium battery diaphragm paper and preparation method thereof
CN110649212A
Preparation method of high-temperature dielectric composite material
CN113183570A
